Comparative analysis between ABNT NBR ISO 9001:2015 and ABNT NBR ISO 31000:2009: the risk mindset in quality management systems - Simão, Victor Gomes (2019)
The new revision of the ISO 9001 standard was launched in 2015 and incorporated new concepts into its collection of requirements for the implementation of a quality management system, such as stakeholder relations, knowledge management, and risk management, broadening its scope of focus. In this sense, and predicting that changes will occur in organizations from this new perspective, this article aims to present the use of risk mentality in quality management systems, through a comparative analysis between the standards ABNT NBR ISO 9001:2015 and ABNT NBR ISO 31000:2009. The research is characterized as qualitative, and was conducted based on documentary research and systematic literature review. The findings suggest that the concept of risk-based thinking has always been implicit in ISO 9001, manifested in the form of preventive actions, and that the intention to incorporate risk thinking as a requirement in the 2015 version is to encourage organizations to take risk as a criterion in their decisions. It is evident that the risk and prevention literature is aligned with the most advanced quality management system methods, which are based more on prevention principles than on corrective actions.